-3=y-4

Simple and best practice solution for -3=y-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=y-4 equation:


Simplifying
-3 = y + -4

Reorder the terms:
-3 = -4 + y

Solving
-3 = -4 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-3 + -1y = -4 + y + -1y

Combine like terms: y + -1y = 0
-3 + -1y = -4 + 0
-3 + -1y = -4

Add '3' to each side of the equation.
-3 + 3 + -1y = -4 + 3

Combine like terms: -3 + 3 = 0
0 + -1y = -4 + 3
-1y = -4 + 3

Combine like terms: -4 + 3 = -1
-1y = -1

Divide each side by '-1'.
y = 1

Simplifying
y = 1

See similar equations:

| (7wz^4)(5w^5z^3)= | | 6x^2+6y^2=150 | | 10+12x+29=180 | | 3(4x+1)=x | | -2-3k=1 | | -15(-18x+21)=9(-3x+229) | | -40=-24t | | 5(a-2)+15=45 | | -15(-18x+21)=(-3x+229) | | 64x+30y=180 | | 24*8= | | i^8= | | h=20-16t^2+32t | | Y=2x^2+8x | | 5/4a+1/2=7/9 | | -6+3n=-7(n+8) | | 5x-4=12-2x | | 10d=200 | | X+0.6y=88 | | 6n-28=-30+4n | | -6+3n=-7 | | 4x+2=6+4x | | 10+d=200 | | -27=6y | | 6y+5=2y+7 | | 25n^2-20n=1 | | 10x-4=11+9x | | -6=z/4 | | x-0.7=8.86 | | 4x-(9-3x)=8x-men | | -13+x=54 | | (X+3)(X+9)=0 |

Equations solver categories